The Influence of Lock-In Centered Business Model Innovation on the Performance of Manufacturing Firms in Kenya - Maundu, Michael; Makau, Godfrey; Wekesa, Susan (European Journal of Business and Strategic Management, 2025)
Purpose: Business model innovation is a fundamental catalyst for organizations to transform their value creation infrastructure in order to achieve superior long-term performance and pay off associated complex commercial risks. This study was designed to investigate the influence of lock-in centered business model innovation on the performance of manufacturing firms in Kenya. Methodology: The study adopted the descriptive research design and positivism philosophy that was aligned to the classical scientific method of research inquiry. Multi-stage sampling method was adopted to collect data from top management team in the manufacturing sector using a semi-structured questionnaire. The data was analysed using descriptive analysis techniques such as mean, percentages and standard deviation. Inferential analysis using linear regression was undertaken to establish the relationship between the predictor variable and the outcome variable using Statistical Package for the Social Sciences software. Findings: The study revealed that lock-in centered business model innovation (β=-0.47, p=0.001<0.05) negatively and significantly influences manufacturing firms’ performance. Unique Contribution to Theory, Practice and Policy: The study recommends that manufacturers should endeavour to innovate their business models in order to achieve superior long-term performance. The study contributes to manufacturing sector literature by providing empirical evidence on how managers can embed business model innovation practices to improve Kenyan manufacturing firms’ performance in the highly volatile, uncertain, complex and ambiguous environment.